5 - Uma longa ambiguidade: minorias sexuais em Moçambique entre tolerância e marginalização - Laura António Nhaueleque, (Africa Development, 2025)
This text aims to address civil associations in Mozambique, focusing on Lambda, an organization founded in 2006, which fights for the defense and recognition of the rights of sexual minorities at the national level. Mozambique decriminalized homosexuality in 2014 and is cited as one of the few tolerant African contexts towards homosexuality. However, Lambda has had a legalisation process pending since 2006, a circumstance that signals an ambiguous stance on the government side towards sexual minorities. The researcher used a qualitative approach, relying on semi- structured interviews with key witnesses and the direct experience of the researcher. It was concluded that associations in Mozambique face major challenges. In the case of Lambda, such elements are even more pronounced, as members of sexual minorities lack acceptance from society and the government, including families who prefer to expel their members, rather than understand and accept their sexual orientation.